Dutch and German 3-year-olds’ representations of voicing alternations - Buckler, Helen; Fikkert, Paula (SAGE, 2015)
The voicing contrast is neutralised syllable and word finally in Dutch and German, leading to alternations within the morphological paradigm (e.g. Dutch ‘bed(s)’, be[t] be[d]en, German ‘dog(s)’, Hun[t]-Hun[d]e). Despite structural similarity, language-specific morphological, phonological and lexical properties impact on the distribution of this alternation in the two languages. Previous acquisition research has focused on one language only, predominantly focusing on children’s production accuracy, concluding that alternations are not acquired until late in the acquisition process in either language. This paper adapts a perceptual method to investigate how voicing alternations are represented in the mental lexicon of Dutch and German 3-year-olds. Sensitivity to mispronunciations of voicing word-medially in plural forms was measured using a visual fixation procedure. Dutch children exhibited evidence of overgeneralising the voicing alternation, whereas German children consistently preferred the correct pronunciation to mispronunciations. Results indicate that the acquisition of voicing alternations is influenced by language-specific factors beyond the alternation itself.